The Mediating Role of Environmental Concern and Perceived Consumer Effectiveness on the Relationship between Consumer Skepticism toward Advertising and Green Purchasing Behavior - Waskito, Jati; Wahyono, W (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2017)
The purpose of this study was to examine the mediating role of Environmental Concern (EC) and Perceived Consumer Effectiveness (PCE) on the behavior of Green Purchasing. Survey with questionnaire instrument involving 299 respondents and using the structural equation model found the skeptical attitude towards direct effect on EC and PCE. PCE becomes a full-fledged mediating role in the influence of consumer skepticism toward advertising and consumer’s green purchasing behavior, unlike the EC that cannot mediate those relationships.